N-Butanol Fraction of Wenxia Formula Extract Inhibits the Growth and Invasion of Non-Small Cell Lung Cancer by Down-Regulating Sp1-Mediated MMP2 Expression - Bi, QianYu; Wang, MengRan; Zhao, Fang; Wang, Meng; Yin, XiangJun; Ruan, JiaZhao; Wang, DeLong; Ji, XuMing (Frontiers in Pharmacology, 2020)
Lung cancer is the most commonly diagnosed cancer and the leading cause of cancer death. It is necessary to develop effective anti-lung cancer therapeutics. Wenxia Formula (WXF), an empirical traditional Chinese herbal formula, has been reported to have significant antitumor activity. In this study, to further clarify the material basis of the anti-tumor effect of WXF, we investigated the cytotoxic effect of the N-butanol fraction of Wenxia Formula extract (NWXF) against two lung cancer and one normal human cell lines. The chemical profile of NWXF was characterized by UPLC/Q-TOF-MS analysis and a total of 201 compounds with mzCloud Best Match of greater than 70 were identified by using the online database mzCloud. To address the functional role of NWXF, we assessed cell proliferation, migration and invasion capabilities. Subcutaneous xenografts were constructed to determine the effect of NWXF in vivo. The results showed that NWXF effectively inhibited the proliferation and migration of non-small cell lung cancer (NSCLC) cells with little toxic effects on human bronchial epithelial cells (HBE). Meanwhile, orally administered NWXF exhibited prominent dose-dependent anti-tumor efficacy in vivo. Mechanistically, NWXF significantly downregulated MMP9 and Sp1-mediated MMP2 expression. In conclusion, NWXF might be a promising candidate for treatment of human lung cancer.